Social Queues (Cues): Impact of Others’ Waiting in Line on One’s Service Time - Ülkü, Sezer; Hydock, Chris; Cui, Shiliang (Management Science, 2022)
The traditional queueing literature assumes that service time is largely independent of social influences. However, queues are social systems; and social considerations are therefore likely to impact customers’ service time decision to the extent they have control. Through a series of experiments, we show that when others are waiting in line, customers tend to accelerate their own service time, and in doing so, sacrifice their own consumption utility. This behavior is driven by concern for others. Notably, the effect is diminished when they themselves have waited, as it is perceived as fair to let others wait if one also had to wait. We further show that obscuring the visibility between customers in service and those waiting in line diminishes the negative effect of others queueing on one’s own service time. This paper was accepted by Jay Swaminathan, operations management. Supplemental Material: Data and the online appendix are available at https://doi.org/10.1287/mnsc.2021.4282 .